Analysis Of Effective Communication On Employee Performance Improvement At PT. Kencana Mulia Abadi Sibolga - Riwayani, Riwayani; Basriyani , Anna; Amelia Gultom , Hesty; Windari , Furi; Sikumbang, Amaludin (Sean Institute, 2025)
Analysis of Effective Communication on Employee Performance Improvement at PT. Kencana Mulia Abadi Sibolga. Performance improvement can be achieved through the implementation of effective communication. This study aims to analyze the impact of effective communication on employee performance improvement at PT. Kencana Mulia Abadi Sibolga. The population in this study consists of all employees of PT. Kencana Mulia Abadi Sibolga, totaling 31 individuals, who were also used as the research sample. Based on the research findings, there is a positive relationship between effective communication and employee performance improvement at PT. Kencana Mulia Abadi Sibolga. This is evidenced by the increase in the number of consumers over the past five years, totaling 310 individuals. The study results indicate a positive correlation between effective communication and employee performance at PT. Kencana Mulia Abadi Sibolga, with a correlation coefficient of 0.757, which, when interpreted on a scale, falls into the moderate category. The regression equation obtained is: Y = 12.491 + 0.637X, which demonstrates the influence of effective communication on employee performance. The t-test results show that the proposed hypothesis is accepted, as t-calculated (6.241) > t-table (2.0452). This means that employee performance increases by the regression coefficient/slope (0.573) for every unit increase in the effective communication variable. Meanwhile, the coefficient of determination reveals that effective communication contributes only 57.3% to employee performance at PT. Kencana Mulia Abadi Sibolga, while the remaining 42.7% is influenced by other factors not examined in this study.